ChemInform Abstract: Reusable Ionic Liquid‐Catalyzed Oxidative Coupling of Azoles and Benzylic Compounds via sp3 C—N Bond Formation under Metal‐Free Conditions. Issue 44 (15th October 2015) - Liu, Wenbo; Liu, Chenjiang; Zhang, Yonghong; Sun, Yadong; Abdukadera, Ablimit; Wang, Bin; Li, He; Ma, Xuecheng; Zhang, Zengpeng
Abstract The scalable reaction procedure is successfully applied to a range of benzotriazoles with 5‐substituted substrates yielding mixtures of regioisomers.